New Headway Upper-Intermediate: Workbook with key - Soars L. Liz (New York, Oxford University Press, 2009)
New Headway is the course teachers and learners can rely hy? An authoritative integrated syllabus, motivating topics and clearly focused tasks combine with a real understanding of what works in the classroom. It all makes for effective teaching and effective learning. Tried and tested all over the world, it's probably the most popular course ever written!